The injection technique: results of a questionnaire study of diabetic patients in Russia. New international guidelines on the injectiontechnique - Olga Georgievna Mel'nikova; Alexander Yur'evich Mayorov (Сахарный диабет, 2010)
Aim. To consider technical aspects of antihyperglycemic injection therapy in patients with type 1 and type 2 diabetes mellitus.Methods. The analysis included 200 adult patients (60 men and 140 women) receiving injection therapy for at least 6 months. They filled a 40-iremquestionnaire designed to estimate socio-demographic parameters, the use of different devices for insulin injection, and the most frequent mistakesmade by the patients. Their mean age was 51.7?15.1 years, duration of DM 11.9?9.1 years, mean HbA1c level 8.4?1.5%. Results. 130 (65%) patients used semiautomated injection pens, 39 (19.5%) disposable syringes, 31 (15.5%) both devices. Most patients (122, 61%)used 8 mm needles, 32 (16%) used 12.7 mm needles, 31 (15.5%) 10 mm, 28 (14%) 12 mm, 19 (9.5%) 6 mm, 18 (9.0%) 5 mm. 64 (32%) patientsused needles of different length, 25 (12.5%) could not give a definitive information about the needle length they used. Location of injection sites variedconsiderably in individual patients. 87 (43.5%) made injections within a single anatomic regions (62 into the anterior abdominal wall, 19 into theanterolateral surface of the thigh, 5 into shoulders, and 1 into buttocks. 113 (56.5%) patients made injections into two or more regions. 83 (41.5%)developed lipodystrophy at injection sites, 42 (50.6%) continued to use them for injections (12 did it on a regular basis and 30 occasionally). HbA1clevels were 9.5 and 8.2% in patients who made injections into affected sites and who had no lipodystrophic changes respectively (p=0.02). Over halfof the interviewed patients (106 or 53%) were informed about correct subcutaneous injection technique by the attending endocrinologist, 60 (30%)were taught by the nursing staff while staying in a hospital or visiting an endocrinological dispensary, 28 (14.%) were educated at Diabetes schools,9 (4.5%) when seeing the local therapist, and 19 (9.5%) by non-professionals. Conclusion. Many patients make serious mistakes when self-administering insulin. Incompliance with the guidelines on insulin injections leading tothe impairment of carbohydrate metabolism, the technical aspects of injections must be in the focus of attention of any practitioner. New (2010) internationalguidelines on the injection technique are overviewed.